P38γ activation triggers dynamical changes in allosteric docking sites - Rodriguez Limardo, Ramiro Gonzalo (2011)
Mitogen-activated protein kinases (MAPKs) are serine-threonine kinases that participate in signal transduction pathways. p38 MAPKs have four isoforms (p38β, p38β, p38γ, and p38δ) which are involved in multiple cellular functions such as proliferation, differentiation, survival, and migration. MAPK kinases phosphorylate p38s in the dual-phosphorylation motif, Thr-Gly-Tyr, located in their activation loop, which induces a conformational change that increases ATP binding affinity and catalytic activity. Several works have proposed that MAPK dynamics is a key factor in determining their function. However, we still do not understand the dynamical changes that lead to MAPK activation. In this work we have used molecular dynamics techniques to study the dynamical changes associated with p38γ activation, the only fully active MAPK crystallized so far. We performed MD simulations of p38γ in three different states, fully active with ATP, active without ATP, and inactive. We found that the dynamical fluctuations of the docking sites, important for protein-protein interactions, are regulated allosterically by changes in the active site. Interestingly, in the phosphorylated and ATP-bound states the whole protein dynamics lead to concerted motions of whole protein domains in contrast to the inactive state. The binding/unbinding of ATP participates in the reorientation of the two domains and in the regulation of protein plasticity. Our study shows that beyond the conformational changes associated with MAPK activation their correlated dynamics are highly regulated by phosphorylation and ATP binding. This means that MAPK plasticity may have a role in their catalytic activity, specificity, and protein-protein interactions and, therefore, in the outcome of the signaling network.